004 Pregnancy-related relapse in natalizumab, fingolimod and dimethyl fumarate-treated women with multiple sclerosis. (23rd August 2021) - Yeh, Wei Z; Widyastuti, Putu A; Walt, Anneke Van der; Stankovich, Jim; Havrdova, Eva K; Horakova, Dana; Vodehnalova, Karolina; Ozakbas, Serkan; Eichau, Sara; Duquette, Pierre; Kalincik, Tomas; Patti, Francesco; et al.
Abstract : Objective: To investigate pregnancy-related disease activity in a contemporary multiple sclerosis (MS) cohort. Methods: Data were obtained from the MSBase Registry. Term/preterm pregnancies conceived from 2011-2019 were included (modern cohort). Annualised relapse rates (ARR) were calculated before, during and after pregnancy. Predictors of intrapartum and early postpartum (1 st 3 months) relapse were determined by clustered logistic and Cox regression analyses, respectively. Results: We included 1640 pregnancies from 1452 women. Disease-modifying therapy (DMT) used in the one-year preconception included natalizumab (n=219), fingolimod (n=147), dimethyl fumarate (DMF; n=57) and low-efficacy therapies (n=845). Preconception ARR by DMT class used before conception were: natalizumab, 0.29 (95% CI 0.22-0.37); fingolimod, 0.37 (0.28-0.49); DMF, 0.24 (0.13-0.41); low-efficacy, 0.29 (0.25-0.33); and none, 0.24 (0.19-0.31). Among women who used fingolimod or natalizumab, ARR increased during pregnancy. Intrapartum ARR decreased in preconception DMF, low-efficacy or no DMT groups. ARR spiked after delivery across all DMT groups. Natalizumab continuation into pregnancy reduced the odds of relapse during pregnancy (OR 0.76 per month [0.60-0.95], p=0.017). DMT re-initiation with natalizumab protected against postpartum relapse (HR 0.11 [0.04-0.32], p<0.0001). Breastfeeding women were less likely to relapse (HR 0.61 [0.41-0.91], p=0.016). Conclusion: Women with MS prescribed natalizumab or fingolimod preconception had higher rates of intrapartum and postpartum relapse. In women considered to be at high relapse risk, use of natalizumab before pregnancy and continued up to 32-34 weeks gestation, with early re-initiation after delivery is an effective option to minimise relapse risks. Strategies of DMT use have to be balanced against potential foetal/neonatal complications.